A reduction approach to prepare ZnSe nanocrystallites - 姜海青 车俊 李智敏 姚熹 (Transactions of Nonferrous Metals Society of China, 2006)
ZnSe nanocrystallites powders were successfully prepared by reduction method with H2SeO4 or H2SeO3 as selenium source and Zn（Ac）2·H2O as zinc source. The reaction mechanism was also discussed through XRD and DTA/TG analysis. In the process, ZnSeO4·H2O or ZnSeO3·H2O crystallites precipitated in organic solvent was prepared at first. Then the crystallites were reduced with carbon monoxide atmosphere. The XRD analysis reveals that the structure of ZnSe phase is sphalerite （cubic ZnS）. The XPS results show that the atomic ratio of Se to Zn is 1 ： 1 approximately. The TEM shows that the size of ZnSe crystallite is 30--50 nm. This method of synthesis of ZnSe nanocrystallites has the potential application in the preparation of optical composite thin films from sol-gel process.